MODIFIKASI GENSET BERBAHAN BAKAR HYBRID DI PILOT PLANT DME BERBAH - Khudhori, Muhrom (Sekolah Tinggi Teknologi Adisutjipto, 2013)
Genset modified with biogas, when biogas empty genset can’t used gasoline. Beside that, when genset operated with biogas are corrosion at fuel system, because in the biogas are water steam. So to solution this problems must to research modifications genset with hybrid fuel (biogas-gasoline). A research with modified on carburetor to assembly venturi mixer. Step a research are engineering design, manufacturing design, and performances test genset modified. Performance parameters are power (watt), voltage (volt), frequency (Hz) and current (ampere). The conclusion of the research are the genset can operate with carburetor modified, and optimum performances at throttle open 25%. On load 0 the result are voltage 212 Volt, frequency 50,9 Hz, current 0,01 A, power 0 watt, with 800 result voltage 196 Volt, frequency 31,5 Hz, current 2,89 A, power 594 watt. Optimum 700 watt with result voltage 217 volt, frequency 44,3 Hz, current 3,09 A, power 694 watt.